2014
DOI: 10.1111/synt.12018
|View full text |Cite
|
Sign up to set email alerts
|

Contrast and Island Sensitivity in Clausal Ellipsis

Abstract: This paper offers a comprehensive and uniform theory of island repair in clausal ellipsis (sluicing and fragments). We show that the correct generalization defines the repairing and the nonrepairing types of TP ellipsis in terms of contrastivity: TP ellipsis with contrastive remnants does not repair islands, whereas TP ellipsis with noncontrastive remnants does. Contrary to the influential account of Merchant (), we base our explanation for the island sensitivity of contrastive fragments entirely on the notion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(38 citation statements)
references
References 54 publications
(103 reference statements)
2
36
0
Order By: Relevance
“…We propose that in most cases, the crucial factor is the form and position of the XP corresponding to the extracted wh-phrase, which we call the correlate. This proposal is broadly in line with the analysis in Thoms to appear b, where similar logic is applied to analyzing very similar restrictions on pseudogapping (see also Griffiths and Lipták 2014).…”
Section: Parallelism and Extraction From Vpsupporting
confidence: 64%
See 2 more Smart Citations
“…We propose that in most cases, the crucial factor is the form and position of the XP corresponding to the extracted wh-phrase, which we call the correlate. This proposal is broadly in line with the analysis in Thoms to appear b, where similar logic is applied to analyzing very similar restrictions on pseudogapping (see also Griffiths and Lipták 2014).…”
Section: Parallelism and Extraction From Vpsupporting
confidence: 64%
“…We argue that this fits with previous work on reconstruction, which has shown that A-movement often seems not to leave a trace (Chomsky 1995, Lasnik 1998, Fox 1999b, Takahashi and Hulsey 2009. Our analysis makes crucial use of a syntactic parallelism condition like the one proposed by Fiengo and May (1994) and Griffiths and Lipták (2014), since the semantic parallelism constraint assumed in the previous MaxElide literature proves insufficiently restrictive.…”
Section: A Number Of Work Have Analyzed the Interactions Between Ellsupporting
confidence: 57%
See 1 more Smart Citation
“…Much work on ellipsis has converged on the conclusion that ellipsis identity is subject to a condition known as Parallelism (Sag , Rooth , Fiengo & May , Fox , Fox & Lasnik , Fox & Pesetsky , Hartman , Griffiths & Lipták , Barker ). Parallelism is motivated by data from scope, and an informal definition of the kind of constraint that is required is given in (30), from Griffiths & Lipták ().…”
Section: Pseudogapping and Parallelismmentioning
confidence: 99%
“…Recall that the correlate of the pseudogapping remnant is always focused. I follow Krifka () and Griffiths & Lipták () in assuming that focused XPs may take scope by covert movement, much like other quantificational elements (see also Chomsky ). Given this, we may say that QR of the correlate to a parallel IP‐internal adjunction position may provide a suitable antecedent for pseudogapping.…”
Section: Pseudogapping and Parallelismmentioning
confidence: 99%